2017
DOI: 10.1002/ejic.201700788
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Equatorial and Oxo Based Influences on Uranyl Vibrational Spectroscopy in a Family of Hybrid Materials Featuring Halogen Bonding Interactions with Uranyl Oxo Atoms

Abstract: Abstract:The syntheses and crystal structures of six new complexes containing the UO 2 2+ cation, m-or p-halobenzoic acid ligands (where halogens are Cl and I), and the chelating Ndonors 1,10-phenanthroline (phen) (1, 3, 4, and 6) or 2,2′:6′,2′′-terpyridine (terpy) (7 and 9) are described and compared to UO 2 -m-bromo-and p-bromobenzoic analogues (2, 5, and 8) that have been reported previously. The spectroscopic properties (both vibrational and luminescence) for all nine complexes along with stretching and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 49 publications
4
20
0
Order By: Relevance
“…As the tectons and topologies observed in 1-4 have precedent in the extensive catalog of uranyl hybrid materials, 3,6,47 we focus our discussion on the modes of supramolecular assembly in these compounds. The supramolecular synthons observed in 1-4 all involve the nominally terminal uranyl oxo atoms, which can be engaged for assembly as we have demonstrated in multiple recent studies, 13,14,16,17 respectively. As there is an increase in halogen polarizability (Br<I) between 3 and 4, halogen bond strengths are not expected to be 'identical,' thus highlighting a limitation with our crystallographic efforts to gauge strengths of halogen-oxo interactions.…”
Section: Structural Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…As the tectons and topologies observed in 1-4 have precedent in the extensive catalog of uranyl hybrid materials, 3,6,47 we focus our discussion on the modes of supramolecular assembly in these compounds. The supramolecular synthons observed in 1-4 all involve the nominally terminal uranyl oxo atoms, which can be engaged for assembly as we have demonstrated in multiple recent studies, 13,14,16,17 respectively. As there is an increase in halogen polarizability (Br<I) between 3 and 4, halogen bond strengths are not expected to be 'identical,' thus highlighting a limitation with our crystallographic efforts to gauge strengths of halogen-oxo interactions.…”
Section: Structural Discussionmentioning
confidence: 84%
“…The uranyl cation is known to feature three characteristic vibrational modes: a symmetric stretching mode (1, 860-880 cm -1 , Raman active), a bending mode (2, 200-210 cm -1 , infrared active), and an asymmetric stretching mode (3, 930-960 cm -1 , infrared active), [48][49][50] and the frequencies of these vibrational modes, in particular 1 and 3, provide valuable spectroscopic information about relative strengths of U=O bonds (which are affected by halogen-oxo interactions). 16,17,27 A look at the Raman and IR spectra of compounds 3 and 4 reveals redshifts (6 cm -1 in the Raman and 11 cm -1 in the IR) with respect to the miodo compound (4) when comparing to the m-bromo compound (3) ( Figure 6). These findings qualitatively illustrate that the iodo-oxo interaction in 4 has a greater effect on the uranyl oxo group, and also suggest that the oxo interactions in 3 and 4 may not be of 'equivalent strength', as suggested by crystallography.…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Using two sets of isomorphous complexes, differing only in halogen atom at the periphery of the tectons, means of assembly were evaluated and results indicated that inclusion of more electron donating N‐donor ligand (i.e. 2,2′:6′,2′′‐terpyridine, rather than 1,10‐phenanthroline) further facilitates halogen bonding at the uranyl oxo atoms . In this study, the spectroscopic manifestations of oxo atom participation in halogen bonding were also explicitly explored and compared to effects that result from equatorial electron donation.…”
Section: Cap‐and‐link Approach To Assembly Via Ncismentioning
confidence: 99%
“…2,2':6',2''-terpyridine, rather than 1,10-phenanthroline) further facilitates halogen bondinga tt he uranyl oxo atoms. [32] In this study,t he spectroscopic manifestations of oxo atom participation in halogen bonding were also explicitly explored and compared to effects that result from equatorial electron donation. Whereas structural resultsi ndicated there wasa ni nterplay between the chelating ligands and benzoic acid groups featuring halogens at the periphery, the polarizabilityoft he selected halogena tom was again found to be mosti mportant for driving the oxo engagement process, and theser esultsr un counter to spectroscopic analysisw hich demonstrates that vibrational (and luminescence) spectra are most impacted by the electrond onating capability of the equatorial ligands.…”
Section: Cap-and-link Approach To Assembly Via Ncismentioning
confidence: 99%